Practice schedules and hierarchical organization in the adaptive process of motor learning - Thiago Oliveira Souza; Umberto Cesar Corrêa (Asociación Española de Ciencias del Deporte, 2020)
The aim of this study was to investigate the effects of different practice schedules on the hierarchical organization of motor skills in the adaptive process. Forty volunteers, both men and women, with an average age of 28.7 years (SD = 8.1) took part in the experiment. The design consisted of two phases (stabilization and adaptation) and four practice groups: constant; constant−random; random; and random−constant. Participants performed 90 trials of golf putting strokes in the stabilization phase and 30 trials in the adaptation phase. Hierarchical organization was accessed by measures of macrostructure (relative displacement and timing) and microstructure (total displacement and time). Cluster analyses were run to infer the emergence of movement patterns over practice. Results showed that constant, random and random-constant groups altered macro and microstructure and improved performance in the stabilization phase. However, their performance worsened after perturbation. It was also verified that consistency of the macrostructure was lower than that of the microstructure. It was concluded that constant, random and random−constant practices made possible the partial formation of the macro and microstructures, since they did not become functional.